Interstitial lung disease in systemic sclerosis quantification of disease classification and progression with high-resolution computed tomography: An observational study. Issue 2 (June 2021) - Clukers, Johan; Lanclus, Maarten; Belmans, Dennis; Van Holsbeke, Cedric; De Backer, Wilfried; Vummidi, Dharshan; Cronin, Paul; Lavon, Ben R; De Backer, Jan; Khanna, Dinesh
Introduction: Systemic sclerosis–associated interstitial lung disease accounts for up to 20% of mortality in these patients and has a highly variable prognosis. Functional respiratory imaging, a quantitative computed tomography imaging technique which allows mapping of regional information, can provide a detailed view of lung structures. It thereby shows potential to better characterize this disease. Purpose: To evaluate the use of functional respiratory imaging quantitative computed tomography in systemic sclerosis–associated interstitial lung disease staging, as well as the relationship between short-term changes in pulmonary function tests and functional respiratory imaging quantitative computed tomography with respect to disease severity. Materials and methods: An observational cohort of 35 patients with systemic sclerosis was retrospectively studied by comparing serial pulmonary function tests and in- and expiratory high-resolution computed tomography over 1.5-year interval. After classification into moderate to severe lung disease and limited lung disease (using a hybrid method integrating quantitative computed tomography and pulmonary function tests), post hoc analysis was performed using mixed-effects models and estimated marginal means in terms of functional respiratory imaging parameters. Results: At follow-up, relative mean forced vital capacity percentage change was not significantly different in the limited (6.37%; N = 13; p = 0.053) and moderate to severe disease (−3.54%; N = 16; p = 0.102) groups, respectively. Specific airway resistance decreased from baseline for both groups. (Least square mean changes −25.11% predicted ( p = 0.006) and −14.02% predicted ( p = 0.001) for limited and moderate to severe diseases.) In contrast to limited disease from baseline, specific airway radius increased in moderate to severe disease by 8.57% predicted ( p = 0.011) with decline of lower lobe volumes of 2.97% predicted ( p = 0.031). Conclusion: Functional respiratory imaging is able to differentiate moderate to severe disease versus limited disease and to detect disease progression in systemic sclerosis.